Pembelajaran Berbasis Masalah Lingkungan (Environment-Based Learning) - Herliyanto, Muci (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2023)
This study aims to analyze the effectiveness of Environment-Based Learning in shaping environmental awareness and eco-friendly behavior among elementary school students. The research uses a library research method with theories of learning as the subject and academic articles related to environment-based learning in elementary schools as the object. Data were collected through document review of accredited national and international journals published in the last five years. The data were analyzed using qualitative content analysis. The results indicate that implementing environment-based learning approaches such as Problem-Based Learning, project-based learning, and outdoor activities significantly enhances students’ engagement, environmental literacy, and problem-solving skills. The study concludes that the success of environment-based learning implementation strongly depends on teacher preparedness, curriculum support, and community involvement